Membingkai âEpistemeâ Ilmu Dakwah - Shodikin, Asep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
One of urgent task in developing science of daâwah is seek what is foundation to it. Because of the foundation so that the science of daâwah having a clear of frame of think. One of the foundations is named epistemology, a foundation of science that study how the science is got and developed. Based on itâs developing, epistemecally the science of daâwah as developed through three methods: dig up the science from Islamic doctrine source and muslim intellectual tradition (thuruqul istinbath), accepting the social science elements and modern technology (thuruqul iqtibash), and a set of research (thuruqul istiqraâ).